Method and apparatus for visualization of database search results - Frank H. Bowers; Stuart K. Card (1996)
A method and apparatus for representing the results of a search of a database. The present invention provides for creating a view of database search results via a tree structure in which detail is selected and context preserved. In the present invention, the tree structure is created based on user specified parameters. These parameters represent attributes of documents stored in the database and may differ from the search parameters. The tree structure is then mapped to a static reference surface which is visually perceived as three-dimensional. The reference surface is comprised of a detail area where detail of the tree structure is displayed and a context area for displaying other portions of the tree in less detail but which conveys to the viewer a sense of context. The tree structure may be scrolled about the reference surface to bring portions of the structure into a direct detail view while retaining a context view of the overall tree.